Loot: How Israel Stole Palestinian Property – book review - John Westmoreland (Counterfire, 2024)
Adam Raz’s Loot contributes important new research on how Israelis plundered and dispossessed Palestinians during the Nakba, finds John Westmoreland Adam Raz has made an important addition to the study of the ethnic cleansing of Palestine in this detailed volume containing original research.